2020
DOI: 10.1016/j.clim.2020.108544
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic blockade of inflammation in severe COVID-19 infection with intravenous N-acetylcysteine

Abstract: Glucose 6-phosphate dehydrogenase (G6PD) deficiency facilitates human coronavirus infection due to glutathione depletion. G6PD deficiency may especially predispose to hemolysis upon coronavirus disease-2019 (COVID-19) infection when employing pro-oxidant therapy. However, glutathione depletion is reversible by Nacetylcysteine (NAC) administration. We describe a severe case of COVID-19 infection in a G6PD-deficient patient treated with hydroxychloroquine who benefited from intravenous (IV) NAC beyond reversal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 64 publications
(79 reference statements)
0
122
4
5
Order By: Relevance
“…However, their efficacy in COVID-19 management is still in its infancy. Moreover, the case studies based on treatments from Imatinib and Colchicine were uncontrolled and restricted in nature ( Della-Torre et al, 2020 ; Ibrahim et al, 2020 ; Morales-Ortega et al, 2020 ). At present, the mainstream therapies are involving aforesaid axis and have proved its significance in the management of CoV-2 replication, but the role of other secondary targets cannot be ruled out in controlling the infection of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, their efficacy in COVID-19 management is still in its infancy. Moreover, the case studies based on treatments from Imatinib and Colchicine were uncontrolled and restricted in nature ( Della-Torre et al, 2020 ; Ibrahim et al, 2020 ; Morales-Ortega et al, 2020 ). At present, the mainstream therapies are involving aforesaid axis and have proved its significance in the management of CoV-2 replication, but the role of other secondary targets cannot be ruled out in controlling the infection of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, glutathione can inactivate dengue and chikungunya viruses in the blood [53,54]. N-acetylcysteine (NAC) attenuates influenza-like symptoms and COVID-19-induced inflammation [55,56]. On the other hand, selenium deficiency in mice is associated with enhanced enteroviruses virulence and the development of myocardial lesions [57,58].…”
Section: Clinical Presentation Of G6pd Deficiency From Classical Drugmentioning
confidence: 99%
“…All the above evidences seem to have a clinical relevance: Polonikov, studying four moderate-severe COVID-19 cases, found that while the three patients with normal/high plasma levels of GSH recovered rapidly, the one with low GSH levels, high plasma ROS and ROS/GSH ratio experienced the most severe illness and, at the date of publication, was still sick (Polonikov, 2020). In another case report, two COVID-19 pneumonia patients were successfully treated with high doses of supplemental intravenous glutathione and oral NAC (Horowitz et al, 2020); finally, Ibrahim et al reported the case of a group of nine severely ill patients successfully treated with NAC (Ibrahim et al, 2020). Notably, these three independent reports-although referring to only fifteen cases-reciprocally strengthen each other in highlighting the relevance of poor GSH levels in COVID-19 clinical progression as well as the importance of maintaining/repleting GSH pools as a countermeasure against SARS-CoV2 virulence.…”
Section: Nsaids Paracetamol and Covid-19mentioning
confidence: 99%